Diversity of trips (Insecta: Thysanoptera: Thripidae) associated with gladiolus in Mexico. (2020)
Gladiolus is a cut flower with the highest year-round demand in Mexico, generating strong economic and social activity. Thrips are the pest that most affects gladiolus and require the most control, but which species cause damage are still unknown. This study aimed to characterize the diversity of thrip species associated with gladiolus cultivation in two production regions of Mexico State. Two plots were established: one in Ixtlahuaca, in the northern part of the state, characterized by less intensive management, and one in Villa Guerrero, in the southeastern part of the state, characterized by intensive management and considered the main production region for ornamentals. Thrips were captured from 100 floral spikes per plot at the end of the cultivation cycle. Results showed the presence of two genera and five species of phytophagous thrips, as well as one predatory thrip genus, in the northern region, while in the southeast region the same two genera were represented but with 12 species, one of which is new for Mexico. Thrips simplex was the most abundant species in both plots evaluated.